Vpliv atorvastatina na trajanje intervala QTc pri bolnikih s srčnim popuščanjem - Goličnik, Alenka (Medicinski razgledi, 2006)
Heart failure is related to QTc interval prolongation and changes in the QRS complex. Recently, elevated plasma levels of brain natriuretic peptide (proBNP) is also being recognized as an important prognostic factor of heart failure. Inhibitors of 3-hydroxy-3-methylglutaryl CoA reductase, statins, might improve general condition and outcome in patients with heart failure. Wehypothesized that short-tenn statin treatment shortens QTc interval durationand has beneficial effects in patients with heart failure. Forty-threepatients with heart failure of ischemic or nonischemic etiology were randomly divided into two groups. The atorvastatin group (n=23) received atorvastatin in a dosage of 10 mg/day for 3 months, while the control group (n=20) did not. After 3 months, QTc interval duration in the avtorvastatin group was significantly shorter compared to baseline (460.30+-34.50 vs. 443.35+-30.35, P10ms) of the QTc interval in the atorvastatin group was associated with improvement in exercise capacity. Plasma levels of proBNP and QRS complex duration did not change significantly during the study and neither did they differ between the groups. Short-term atorvastatin treatment shortens QTc interval duration in patients with heart failure and is related to improved exercise capacity, without affecting QRS complex duration or plasma levels of proBNP. QTc interval shortening is related to improvements of exercise capacity in patients with heart failure.
Keywords: Elektrokardiografija; Heart Failure, Congestive; Hidroksimetilglutaril CoA reduktaze; Electrocardiography; Hydroxymethylglutaryl Coa Reductases; Srce, odpoved kongestivna; srčno popuščanje; Antagonists And Inhibitors; therapy; zdravljenje; statini